Assessment of hip abductors by MRI after total hip arthroplasty and effect of fatty atrophy on functional outcome - Emrah Kovalak; Hanife Özdemir; Cenk Ermutlu; Abdullah Obut (Acta Orthopaedica et Traumatologica Turcica)
Objectives: The aim of this study was to evaluate how fatty atrophy (FA) of the hip abductors in operated and non-operated hips affected the functional outcome following arthroplasty. Methods: Forty-four hips of 22 patients (8 males and 14 females; mean age: 60 ± 14.4 (range: 24–84)) who matched the inclusion criteria and willing to participate in the study were retrospectively evaluated. The mean follow-up was 13.8 ± 2.3 (range: 10–18) months Magnetic resonance imaging (MRI) and Harris Hip Score (HHS) were used to evaluate muscle degeneration and functional outcome after unilateral THA through a posterolateral approach. The FA grade was evaluated using Goutallier grading system. Non-operated hips of subjects were used as the control. Age, duration after the operation, gluteal muscle FA, and the relationships with HHS were evaluated. Results: FA was more evident in the operated hip (p < 0.05), and was more in the gluteus minimus than in the gluteus medius in both hips (p < 0.05). Patients' age was not correlated with gluteal muscle FA in the operated hip (p > 0.05), whereas there was a positive correlation with the contra-lateral hip (p < 0.05). Duration after surgery did not affect gluteal muscle FA in the operated hip. Older age and FA of either the operated or healthy hip resulted in poorer HHS (p < 0.05). HHS had the strongest correlations with patient age (p < 0.001) and FA (p = 0.026) of the gluteus minimus of contralateral hip. Conclusion: Following THA, there was marked FA in the operated hip compared to that in the contralateral hip. In these cases, degree of FA in the replaced hip did not correlate with patients' age. Fatty atrophy of the gluteus minimus precedes that of gluteus medius. FA of the contralateral gluteus minimus and patient age are strongly correlated with lower HHS. Level of evidence: Level IV, diagnostic study. Level of evidence: Level IV, diagnostic study. Keywords: Total hip arthroplasty, Fatty atrophy, Hip abductor muscles, Magnetic resonance imaging, Functional outcome